A high-efficiency and stable transfection approach by using calcium phosphate in HEK293T cells - Kuang Ye; Fang Yourong; Liu Li; Wang Rong; Yan Ziqin; Li Hailong; Meng Fanguo; Sheng Qing; Ou Wenbin (浙江大学学报. 农业与生命科学版)
Transfection, involving the transfer of exogenous DNA to eukaryocyte cells, is a common technique in molecular and cellular biology, including calcium phosphate transfection, electroporation, lipofection and so on. Calcium phosphate transfection is one of the major methods for DNA transfer to eukaryocyte cells and with lower toxicity and cost than lipofection. However, the application of calcium phosphate transfection method was limited due to its low transfection efficiency and instability.To establish a highly efficient and stable transfection approach to overexpress exogenous protein abundantly in HEK293T cells in vitro, green fluorescent protein (GFP) plasmid DNA was transfected by using calcium phosphate with optimal DNA amount and vortex time of calcium phosphate-DNA complex in absence or presence of common transfection enhancers including glycerol, sodium butyrate, and chloroquine.The protocol of calcium phosphate transfection was as follows. First, HEK293T cells were seeded in a sixwell plate, incubated for 8-24 hours at 37℃ in a humid incubator with 5% CO2, and then the cells were transfected after cell confluence reached 50%-80%. Second, calcium phosphate-DNA complex was prepared. Mixed GFP DNA plasmid with 25 μL of 2.5 mol/L CaCl2 solution in a round-bottom tube, added sterile water up to 250 μL, blended 10 μL of phosphate-solution [V(70 mmol/L Na2HPO4)∶V(70 mmol/L NaH2PO4)=1∶1] with 250 μL of 2×Hepes buffer solution and added to the former solution, added calcium phosphate-DNA mixture into HEK293T cells one drop at a time immediately after vortex. Finally, transfection efficiency was detected by fluorescence imaging in absence or presence of common transfection enhancers including glycerol, sodium butyrate, and chloroquine. The dosage of DNA, duration of vortex and concentrations of three common transfection enhancers were optimized during or after transfection.The results showed that the optimal GFP plasmid DNA amount was 3 μg/well. Compared with GFP plasmid DNA amount of 1 or 2 μg/well and 4 or 5 μg/well, average transfection efficiency of optimal amount was improved by 50% and 70%, respectively. Higher transfection efficiency was also detected when the vortex time was 10 s. Under these optimal conditions, transfection efficiency of treatment with 15% glycerol alone for 6.5 min was significantly higher than that for 2.5, 4.5, 8.5, or 10.5 min. When the HEK293T cells were treated with the combination of 15% glycerol with 5 mmol/L sodium butyrate or 500 μmol/L chloroquine alone, transfection efficiency was improved by 80% and 75%, respectively. Meanwhile, GFP fluorescence intensity was enhanced.Compared to lipofectamine reagents, calcium phosphate transfection with enhancers is more efficient, less toxic and less expensive. Therefore, this approach can be used to overexpress large-scale proteins in the HEK293T cells in vitro, or to package lentiviruses/retroviruses. It is especially applicable for in vitro high flux expression and preparation for various glycosylated proteins such as cancer diagnosis markers.